The international dimension of an incomplete EMU - Demosthenes Ioannou; Maria Sole Pagliari; Livio Stracca (European Central Bank (ECB), 2020)
This paper quantifies the economic influence that shocks to EMU cohesion, which in turn reflect the incomplete nature of the monetary union, have on the rest of the world. Disentangling euro area stress shocks and global risk aversion shocks based on a combination of sign, magnitude and narrative restrictions in a daily Structural Vector Autoregression (VAR) model with financial variables. We find that the effects of euro area stress shocks are significant not only for the euro area but also for the rest of the world. Notably, an increase in euro area stress entails a slowdown of economic activity in the rest of the world, as well as a fall in imports/exports of both the euro area and the rest of the world. A decrease in euro area stress has somewhat more widespread beneficial effects on both economic performance and global trade activity.
Keywords: C23; C32; F02; F33; 330; Economic and Monetary Union; Bayesian SVAR; narrative sign restrictions; panel local projections